2010
DOI: 10.2746/042516406776563332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical findings, diagnosis, prevalence and predisposing factors for lameness localised to the middle carpal joint in young Standardbred racehorses

Abstract: Summary Reasons for performing study: Lameness related to the middle carpal joint (MCJ) occurs in up to 30% of young Standardbred horses in race training and the incidence increase with radiographic severity of third carpal bone (C3) sclerosis on DPr‐DDIO (skyline) view of the carpus. Factors predisposing horses to carpal injury have not been well investigated. Objectives: To determine the importance of MCJ lameness as a cause of wastage in young Standardbred racehorses, stage of training at which it occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
1
23
0
Order By: Relevance
“…Supporting our findings, a study on middle carpal joint lameness in STBR showed that a higher incidence of third carpal bone pathology was not related to more intense exercise programs [8]. In contrast, epidemiological studies in young TBR demonstrated that different trainers were correlated with different MSI IRs [5,6].…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Supporting our findings, a study on middle carpal joint lameness in STBR showed that a higher incidence of third carpal bone pathology was not related to more intense exercise programs [8]. In contrast, epidemiological studies in young TBR demonstrated that different trainers were correlated with different MSI IRs [5,6].…”
Section: Discussionsupporting
confidence: 80%
“…Musculoskeletal injuries (MSI) are the primary cause of reduced training days and racehorse wastage in Standardbred racehorses (STBR) as well as in Thoroughbred racehorses (TBR) [1-6]. But, only a few research studies have attentively focused on STBR specific problems [7-10], such as middle carpal joint injuries [8] and proximal sesamoid bone fractures [9]. Large-scale studies on exercise-related MSI in this population are missing, compared to TBR, probably because in STBR catastrophic events are rare during competitions, thus not raising welfare concerns on racecourse safety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limited reports indicate that the risk is greatest with training programmes that are most intense in terms of weekly duration and weekly duration of exercise performed at maximal effort. 29,30 A training program with a 30% reduction in the highintensity distance covered during the first few years of training in Swedish Standardbreds was equally as effective in achieving performance goals and was associated with fewer lost training days. 31,32 Variation in training (cross-training) reduced the days-lost to training and competition from orthopaedic injury in elite showjumpers, 33 yet benefits of variation in activity have not been studied in Standardbreds.…”
Section: Discussionmentioning
confidence: 99%